Nanoparticle technologies for liver targeting and their applications in liver diseases - Peng, Mengjia; Fang, Fei; Wang, Bowen (Frontiers in Bioengineering and Biotechnology, 2025)
Liver diseases represent a significant global health challenge, affecting millions of lives annually. The advent of nanoparticle (NP) technologies has introduced promising therapeutic strategies for addressing liver diseases. Given the liver’s pivotal role in detoxification and the inherent ability to interact with circulating NPs, it emerges as an ideal target for NP-mediated therapies. Upon systemic administration, NPs predominantly accumulate within the liver, where they are uptaken and internalized by hepatic macrophages, sinusoidal endothelial cells, and hepatocytes. This natural tropism of NPs toward the liver highlights their potential for targeted liver disease management. This review describes the physiological conditions of the hepatic sinusoids and elucidates the interactions between various hepatic cells and NPs. A thorough understanding of these physiological mechanisms is essential for optimizing liver-targeted NP delivery systems, thereby improving NP accumulation at pathological sites. The development of liver-targeted NPs technologies holds immense promise for both the diagnosis and treatment of liver diseases.